Salvia rosmarinus Spenn. Main Applications and Ultrasonic Extraction of Secondary Metabolites: a General Review - Cedillo-Portillo, José Juan; Villastrigo-López, Wendy Yaneth; Castañeda-Facio, Adali Oliva; Esparza-González, Sandra Cecilia; Múzquiz-Ramos, Elia Martha; Sáenz-Galindo, Aidé (Revista Mexicana de Ingenieria Biomedica, 2024)
This paper provides an overview of the various applications of the bioactive compounds found in S. rosmarinus. at present. Additionally, it explores emerging technologies for its extraction, such as ultrasound, which is an effective, fast, and sustainable technology for obtaining these secondary metabolites from this millenary plant. S. rosmarinus has gained considerable importance due to its beneficial properties, including antimicrobial, antioxidant, hepatoprotective, anti-inflammatory, and anticarcinogenic effects. These effects result from the different metabolites, which, without the use of ultrasound, are produced in S. rosmarinus. The main objective of this research is to provide an overview of some of the main applications in which S. rosmarinus is involved and to present a viable and effective alternative for the extraction of the different metabolites it contains using a technique such as ultrasound. The literature review was performed by searching for information on digital platforms such as SciFinder, PubMed, Scopus, and ScienceDirect, using keywords such as Rosemary, S. rosmarinus, ultrasound, green extraction, and secondary metabolite.